Is there a role for shared decision-making in pediatric weight management?. Issue 2 (March 2018) - Kebbe, Maryam; Perez, Arnaldo; Ball, Geoff D.C.
Summary: Shared decision-making (SDM) is central to personalising health and medical decisions. This decisional model encourages patients to act as managers of their own care while maintaining a partnership with health professionals. Although applied to some conditions, SDM has been used infrequently in pediatric weight management (PWM). Herein, we highlight the applicability and usefulness of SDM in making several important decisions related to PWM, including referral-making to different levels of care and treatment initiation and implementation. We conclude by describing possible challenges that may arise when implementing this model and suggest strategies to optimise the use of SDM in PWM.